2023
DOI: 10.1159/000529171
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of miR-124a Expression in Peripheral Blood and Synovial Fluid of Patients with Rheumatoid Arthritis

Abstract: Introduction: Rheumatoid arthritis (RA), a chronic autoimmune disorder, is currently a severe health threat. Previous studies have documented the altered expression of various miRNAs in RA patients. This study determined the expression of miR-124a in RA patients and estimated its diagnostic value for RA. Methods: Total 80 RA patients were enrolled as the study subjects and 36 patients with osteoarthritis were included, with another 36 healthy people as the controls. miR-124a expression levels in peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Moreover, an early study demonstrated that miR-124a can suppress proliferation through the interaction with cyclin-dependent kinases (CDKs) [73]. Due to the downregulation of miR-124a in plasma, peripheral blood mononuclear cells (PBMC) and synovial fluid, as well as negative correlations with clinical parameters, it has been proposed that miR-124a could be used in the diagnosis process of RA [74]. In addition, exosomes derived from chondrogenic bone marrow stem cells contain miR-205-5p, which targets MDM2 and reduces inflammatory responses in FLSs.…”
Section: Mesenchymal Stem-cell-derived Extracellular Vesicles and Fib...mentioning
confidence: 99%
“…Moreover, an early study demonstrated that miR-124a can suppress proliferation through the interaction with cyclin-dependent kinases (CDKs) [73]. Due to the downregulation of miR-124a in plasma, peripheral blood mononuclear cells (PBMC) and synovial fluid, as well as negative correlations with clinical parameters, it has been proposed that miR-124a could be used in the diagnosis process of RA [74]. In addition, exosomes derived from chondrogenic bone marrow stem cells contain miR-205-5p, which targets MDM2 and reduces inflammatory responses in FLSs.…”
Section: Mesenchymal Stem-cell-derived Extracellular Vesicles and Fib...mentioning
confidence: 99%